2022
DOI: 10.1021/acsami.1c23102
|View full text |Cite
|
Sign up to set email alerts
|

Super-Strong, Nonswellable, and Biocompatible Hydrogels Inspired by Human Tendons

Abstract: Fabricating artificial materials that mimic the structures and properties of tendons is of great significance. Possessing a tensile stress of approximately 10.0 MPa and a water content of around 60%, human tendons exhibit excellent mechanical properties to support daily functions. In contrast to tendons, most synthetic hydrogels with similar water content typically exclude qualified strength, swelling resistance, and biocompatibility. Herein, a facile strategy based on poly­(vinyl alcohol) (PVA) and tannic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 69 publications
2
52
0
Order By: Relevance
“…However, it has been proved by Pan et al that single PVA hydrogels do not efficiently support cell proliferation and lack antibacterial activity and elasticity [ 46 ]. Using cross-linking agents and combining PVA with natural polymers to improve their biological properties are current trends [ 46 , 47 , 48 , 49 , 138 ]. As to biological features, PVA-based hydrogels containing diphlorethohydroxycarmalol (DPHC) have been developed by Kim et al (2020) for wound healing applications, whose in vitro and in vivo evaluation on ICR mice demonstrated interesting antimicrobial properties against S. aureus and P. aeruginosa [ 50 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, it has been proved by Pan et al that single PVA hydrogels do not efficiently support cell proliferation and lack antibacterial activity and elasticity [ 46 ]. Using cross-linking agents and combining PVA with natural polymers to improve their biological properties are current trends [ 46 , 47 , 48 , 49 , 138 ]. As to biological features, PVA-based hydrogels containing diphlorethohydroxycarmalol (DPHC) have been developed by Kim et al (2020) for wound healing applications, whose in vitro and in vivo evaluation on ICR mice demonstrated interesting antimicrobial properties against S. aureus and P. aeruginosa [ 50 ].…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that the obtained gel was suitable for cartilage substitutes (compressive strength around 10 MPa). The fracture energy and the fatigue threshold were estimated to be 47.4 kJ/m 2 and 715.3 J/m 2 for the J-HPCS-HAp gel (Figure S10), respectively, among top value of PVA hydrogels. , To compare our results with reported cartilage replacements, their performances were summarized in Figure d and Table S2. ,,,,, Clearly, the J-HPCS-HAp hydrogel was superior to the current hydrogels, especially in a combination of high strength, remarkable swelling resistance, low FC and osteoinductivity potential.…”
Section: Resultsmentioning
confidence: 81%
“…Mass ratios of C and O near the surface (47.88, 52.12%) were close to that at the middle (47.92, 52.08%), indicating even distribution. 7,35 Considering the ionic interactions are universal, we also immersed PVA/CS aerogel in aqueous solutions of sodium alginate (SA) and poly(acrylic acid) (PAAc). As shown in Figure S4, although the compressive strength and modulus of the PVA-CS-SA, PVA-CS-PAAc composited gels were better than the resultant HPCS pregel, their FCs were higher than the resultant HPCS pregel, due to the decline in water contents.…”
Section: Preparation and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Thereby, the mechanical gradient strategy of ICs (rigid)-PVA glue (high elastic modulus)-TPU nanofiber substrates (low elastic modulus)-LM (liquid) can be used to adapt the stretching of the devices. TPU is a commonly used elastic polymer in various industries due to its excellent mechanical and anti-biochemical properties. , Gallium-based LM is also favored by flexible electronics researchers due to its low toxicity, high electrical conductivity, and strong ductility. PVA is the main ingredient in many commercial types of glue, which has excellent biocompatibility. , Its aqueous solution will become a flexible membrane with a high elastic modulus after drying. Through these mechanical gradients, we obtain ultra-stretchable (900%) flexible electronic devices with particularly stable and reliable joints, which also have good comfort, safety, and multilayer structure.…”
Section: Introductionmentioning
confidence: 99%